Art, not a science: How legal impact organizations identify community need. (10th May 2022) - Trowbridge, David
Abstract: The cause lawyering and social movement organization literature explains that movement groups may not prioritize needs that are important to marginalized subgroups within their constituencies. This echoes common and salient critiques within the LGBTQ legal industry. Using a case study of legal organizations within the LGBTQ movement, this article attempts to identify the mechanisms used to determine community need. Contrary to expectations, legal organizations take deliberate and often systematic steps to understand community need and recognize it as central to priority setting. Information flow about needs between large impact groups and smaller state/local groups moves in both directions. However, there are features of these mechanisms that may explain the perceived gap between organizational agendas and community need. The identification of sites and tools for determining need found in this project might provide organizations with guideposts to help them improve practices and close that gap. Finally, the findings here add to our understanding of how lawyers seek to promote organizational accountability.